Heritage-Driven Revitalization of Indrapurwa Mosque: A Conceptual Design Study - Shara, Siti; Zahriah, Zahriah; Wulandari, Elysa; Djamaluddin, Masdar; Maharani, Lisa (Grimsa Journal of Science Engineering and Technology, 2026)
The Indrapurwa Mosque, located in Lamguron Village, Aceh Besar, Indonesia, is a significant historical site dating back to the Aceh Sultanate period. However, following the 2004 earthquake and tsunami, the mosque has experienced physical degradation and diminished public recognition. As part of the historical spatial network of Aceh Lhee Sagoe, the mosque requires a systematic and context-sensitive preservation approach to safeguard its historical and cultural values. This study aims to formulate a revitalization concept for the Indrapurwa Mosque complex by using its original architectural character as the primary design foundation. This research employs a qualitative descriptive method, integrating field observations, interviews, and historical literature review. The study is conducted in two main stages. The first stage involves identifying and analyzing the architectural character of the original Indrapurwa Mosque, including its tiered (tumpang) roof typology, structural system, materiality, and spatial organization. The second stage translates these characteristics into design parameters for the revitalization of the mosque complex, adapted to contemporary functional and spatial requirements. The findings demonstrate that integrating traditional Nusantara architectural character into the design framework can effectively restore the identity of the Indrapurwa Mosque while maintaining historical continuity. The proposed revitalization concept balances preservation and development by reinterpreting architectural values into a contemporary context. This research contributes both theoretically and practically, offering a character-based revitalization approach and providing a reference for the design and preservation of historic religious architecture in Aceh that is rooted in local cultural heritage.